Electrical properties of interdigitated partially bent like shaped liquid crystalline compound. (3rd May 2017) - Bhattacharjee, Debanjan; Alapati, Parameswara Rao; Bhattacharjee, Ayon
ABSTRACT: This article represents the electrical studies of an interdigitated highly skewed N(4-n-pentyloxybenzylidene) 4-n-alkylaniline (5O.16) compound. Interestingly the compound is partially bent like and unsymmetrical in alkyl chain length. Dielectric and impedance spectroscopy studies indicate the coupling between the liquid crystal and the electrical field. Studies were carried out as a function of temperature as well as frequency. Semicircular nature of the Cole–Cole plots indicates the reorientation of the molecule with the applied field. Using the experimental data and the theoretically fitted results the effective equivalent model circuit was designed. Which used to explain the behavior of the compound under the external electric effect and the influence of the electrodes with different variable represent the resistor circuit. However, the effect of the conductivity of temperature and frequency are also reported.